ISSU-ISSU PENELANTARAN, PENGUCILAN DAN KERENTANAN ANAK DI JAKARTA BARAT - Anwar Sitepu; Irmayani Irmayani (Puslitbangkesos Kementerian Sosial RI, 2010)
The study shows that in West Jakarta, there are many children experience deprivation, exclusion and vulnerability (DEV). Children do not acquire their rights to grow and develop optimally, apprehensive, because it all stake holders need to work harder. Deprivation issues that stand out are: children are not brought to the neighborhood health center, infants not given breast milk (milk), exclusively, infant malnutrition / malnutrition, children do not have access to early childhood education (ECD), children do not have birth certificates and school dropouts. Exclusion of important issues are: poor children excluded from education, children are employed, the daughter of high school is deemed not necessary. While the issue of vulnerability of children is: dropout-prone, vulnerable to contracting communicable diseases, prone to become victims of disaster, prone to become victims of bad influence of the environment, prone to become victims of crime. DEV in West Jakarta due to a variety of interrelated reasons (complex) such as: lack of knowledge and awareness of parents, poverty, divorce and lack of public service facilities and the lack of security and social protection. Family as the first and foremost responsible for the development of the child fails to perform its function properly.